Mechanisms for the prevention of poverty trap in minimum income benefits - Zalakain Hernández, Joseba (Cuadernos de Relaciones Laborales, 2021)
In order to contribute to the design of mechanisms for preventing the poverty trap in min-imum income systems, this article analyses the treatment currently given to wage income in regional minimum income systems and compares the impact of five income support models on that poverty trap. The article shows that the logic of preventing the poverty trap is making its way, with difficulty, into the space of the Spanish regional minimum income guarantee systems. The analysis carried out also shows that the unconditional, universal and individual Basic Income (UBI) is not, in essence, more useful than the minimum in-comes in terms of preventing the poverty trap, since its usefulness in this respect does not depend on its greater or lesser conditionality, but on other factors such as the guaranteed amounts and the income tax rates applied.